(untitled) (Historia, 2021)
The name "Soweto" is an international household word but, staggeringly, a systematic history of the place and its people has never been attempted. Soweto A History makes no claim to fill this gap. Indeed, with a total length of 162 pages, of which almost half is taken up by photographs, it could hardly hope to do so. It is, however, a very welcome beginning.